Alkaline Earth Metal Complexes: Mixed Ligand complexes of Alkaline Earth Metal Salts of Some Organic acids with Naturally Occurring Substrate - Prakash, D.; Singh, R.N.; Gupta, O.P.; Kumar, S.B. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of alkaline earth metal salts of organic acid viz., o-nitrophenol, 1-nitroso-2-naphthol, 8-hydroxyquinoline, o-aminobenzoic acid, salicylic acid, salicylaldehyde and acetyl acetone with 5-hydroxy-1,4-naphthaquinone (Juglone) have been synthesised and characterised on the basis of elemental analysis, conductivity measurement and infrared spectral data. The probable structure has also been assigned.